(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Landslides are a common hazard in the Chittagong Hill Tracts (CHT) area in Bangladesh. The communities who are usually live on hill slopes in CHT repeatedly experience landslide hazards during the rainy season with casualties,economic losses and property damages.The present study was conducted in 4 wards of Bandarban municipality to assess the landslide vulnerability of existing urban hills in perspective of hill cutting. An Environmental Impact Assessment (EIA) was conducted to know the impacts of landslides on local environment. Both the primary and secondary sources of data have beenincorporated to achieve the findings of the study.Primary data were collected through direct field observation survey, questionnaire survey, focus group discussion (FGD) and experts’ opinion survey. The questionnaire survey was conducted on 280 respondents selected randomly from the study area. Secondary data were collected from various official records,reports of various government and non-government organization,researcher articles and internet sources. The present study indicated that Kalaghata (Ward No-3) and BandarbanSadar (Ward No-4) are highly vulnerable landslide prone areas in Bandarban municipality.Rapid urbanization has been driven to accelerate hill-cutting activities in the study area. Survey study also indicated that political leaders and influential businesspersons are highly responsible for illegal hill cutting for their own benefits that isacting as triggering factors along with torrential rainfall.The summarized Environmental Impact Values (EIVs) through EIA regarding urban environmental parameters are calculated as negative(-Ve) all specific area (ie. There are no positive impacts of hill cutting activities on local urbanenvironment in the study area).The summarized EIVs for urban environmental parameters are observed negatively highest at Kalaghata (-145)followed by Balaghata (-107), Bandarbansadar(-105) and Islampur(-92) ward in the study area. The Chittagong Univ. J. B. Sci. 9(1&2):99-118,2019